ANALISIS NILAI PENTING GULMA PADA TANAMAN PADI DALAM RANGKA PEMILIHAN PENGENDALIAN RAMAH LINGKUNGAN - Hoesain, Mohammad; Hasjim, Syaifuddin; Widodo, Nur; Harsita, Pradiptya Ayu (Fakultas Pertanian Universitas Mahasaraswati Denpasar, 2019)
Weeds is crops that can compete, disturb and reduce total of rice plants production. The purpose of this research was to determine the important value index of weeds on rice plants. Research method is used vegetative analysis with square method, vegetative and generative phase. Parameters that are observed were Density (K), Relative Density (KR), Frequency (F), Relative Frequency (FR), Important value Index (IVI). Result of the research showed that type of weed in rice plants vegetative phase were had highest score consecutively are Fimbristylis miliacea (L) Vahl.58.26; Hydrolea spinosa L. 39.57:Sphenoclea zeylanica Gaertn 39.40;. While, type of weeds in generative phase results are Leptochloa chinensis (L) Ness 60.88; Fimbristilis milaceae (L) Vahl 56.82; Cyperus iria L. 38.65.  In based on the important value of weed of environmental friendly control includes pre-planting land processing, floading of several days in the vegetative phase and weeding.